KOMUNIKASI INTERPERSONAL ORANG TUA DAN ANAK MENUJU KELUARGA TENANG DAN HARMONIS - Sun Fatayati (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2012)
Communication is the main part of human life. Trough communication, people can express what they think and what they feel to some body else. They can also transmit message, persuade, negotiate and persuade other people. In marriage relationship communication plays an important role in maintaining a good relationship among members of the family especially husband and wife. A study reports that there were many couples aside having problem with their marriage due to their unability to build inter-personal communication between them. This paper argue’s that in order to have a harmonious family, husband and wave need to built interpersonal communication shill.